Hepatocyte nuclear factor 4α controls iron metabolism and regulates transferrin receptor 2 in mouse liver - Matsuo, Shunsuke; Ogawa, Masayuki; Muckenthaler, Martina; Mizui, Yumiko; Sasaki, Shota; Fujimura, Takafumi; Takizawa, Masayuki; Ariga, Nagayuki; Ozaki, Hiroaki; Sakaguchi, Masakiyo; Gonzalez, Frank J.; Inoue, Yusuke (JBC papers in press, 2015)
Iron is an essential element in biological systems, but excess iron promotes the formation of reactive oxygen species, resulting in cellular toxicity. Several iron-related genes are highly expressed in the liver, a tissue in which hepatocyte nuclear factor 4α (HNF4α) plays a critical role in controlling gene expression. Therefore, the role of hepatic HNF4α in iron homeostasis was examined using liver-specific HNF4α-null mice (Hnf4aΔH mice). Hnf4aΔH mice exhibit hypoferremia and a significant change in hepatic gene expression. Notably, the expression of transferrin receptor 2 (Tfr2) mRNA was markedly decreased in Hnf4aΔH mice. Promoter analysis of the Tfr2 gene showed that the basal promoter was located at a GC-rich region upstream of the transcription start site, a region that can be transactivated in an HNF4α-independent manner. HNF4α-dependent expression of Tfr2 was mediated by a proximal promoter containing two HNF4α-binding sites located between the transcription start site and the translation start site. Both the GC-rich region of the basal promoter and the HNF4α-binding sites were required for maximal transactivation. Moreover, siRNA knockdown of HNF4α suppressed TFR2 expression in human HCC cells. These results suggest that Tfr2 is a novel target gene for HNF4α, and hepatic HNF4α plays a critical role in iron homeostasis.